Mutations in the SmAPRR2 transcription factor suppressing chlorophyll pigmentation in the eggplant fruit peel are key drivers of a diversified colour palette - Arrones, Andrea; Mangino, Giulio; Alonso, David; Plazas, Mariola; Prohens, Jaime; Portis, Ezio; Barchi, Lorenzo; Giuliano, Giovanni; Vilanova, Santiago; Gramazio, Pietro (Frontiers in Plant Science, 2022)
Understanding the mechanisms by which chlorophylls are synthesized in the eggplant (Solanum melongena) fruit peel is of great relevance for eggplant breeding. A multi-parent advanced generation inter-cross (MAGIC) population and a germplasm collection have been screened for green pigmentation in the fruit peel and used to identify candidate genes for this trait. A genome-wide association study (GWAS) performed with 420 MAGIC individuals revealed a major association on chromosome 8 close to a gene similar to APRR2. Two variants in SmAPRR2, predicted as having a high impact effect, were associated with the absence of fruit chlorophyll pigmentation in the MAGIC population, and a large deletion of 5.27 kb was found in two reference genomes of accessions without chlorophyll in the fruit peel. The validation of the candidate gene SmAPRR2 was performed by its sequencing in a set of MAGIC individuals and through its de novo assembly in 277 accessions from the G2P-SOL eggplant core collection. Two additional mutations in SmAPRR2 associated with the lack of chlorophyll were identified in the core collection set. The phylogenetic analysis of APRR2 reveals orthology within Solanaceae and suggests that specialization of APRR2-like genes occurred independently in Cucurbitaceae and Solanaceae. A strong geographical differentiation was observed in the frequency of predominant mutations in SmAPRR2, resulting in a lack of fruit chlorophyll pigmentation and suggesting that this phenotype may have arisen and been selected independently several times. This study represents the first identification of a major gene for fruit chlorophyll pigmentation in the eggplant fruit.